2017
DOI: 10.1016/j.ijnurstu.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of approaches used to teach quality improvement to pre-registration healthcare professionals: An integrative review

Abstract: Evaluating quality improvement education is complex. Experiential learning combined with didactics is the favoured approach; however, attributing causality to educational intervention proves difficult in light of poor methodological rigour, lack of validated tools and complex clinical settings. Clarity regarding which quality improvement competencies are priority for this population would be useful to streamline future educational development and evaluation. Stronger collaboration between educators and clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Second, our findings may not be readily applicable to other settings. Although nursing students have been the target of many curricular efforts (L. Armstrong, Shepherd and Harris, 2017), only 5% of participants in our pilot were nursing students. We hypothesize that reasons for the low level of nursing engagement are likely multifactorial, with barriers including busy academic schedules and limited numbers of nursing faculty with PS and QI expertise available to mentor and promote this work to students.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, our findings may not be readily applicable to other settings. Although nursing students have been the target of many curricular efforts (L. Armstrong, Shepherd and Harris, 2017), only 5% of participants in our pilot were nursing students. We hypothesize that reasons for the low level of nursing engagement are likely multifactorial, with barriers including busy academic schedules and limited numbers of nursing faculty with PS and QI expertise available to mentor and promote this work to students.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A number of reviews describing various PS and QI curricula and their impacts on health professions students have emerged over the last decade (Wong et al, 2010;L. Armstrong, Shepherd and Harris, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Based on the above explanation, it can be concluded that Donald Kirkpatrick's evaluation model is one of the most popular evaluation models for measuring training effectiveness. This model has 4 levels of level; level 1 (reaction) consists of facilities and infrastructure, materials/curriculum, instructor, supervision and schedule, level 2 (learning) consists of mastery of the material, and the activity of the participants, level 3 (behavior) consists of behavior change, level 4 (result) consisting of productivity and performance.METHODOLOGYThis evaluation study uses an evaluative research model with Kirkpatrick evaluation model.…”
mentioning
confidence: 99%